The Differences of the Behavioral Factors of Midwifes in UCI village and non UCI - Wati, Siti Fatma; Wahjuni, Chatarina Umbul (Jurnal Berkala Epidemiologi, 2014)
ABSTRACT2-3 millions of people in all groups of age die every year caused by the diseases that can be prevented by immunization: diphtheria, pertussis, tetanus and measles. It is due to the UCI village target from year to year are not increased properly. One of the reasons of the unattainable UCIâs target is due to the factor of the officers. This research aims to determine the differences of the characteristic and the behavioral of the officers in UCI village as well as non-UCI in the District of Pasuruan (Kabupaten Pasuruan). The research is conducted by using the design of cross sectional. The samples in this study were 76 village midwifes. Sampling was stratified random sampling method. Data were analyzed using chi square statistical test. The independent variabel is the status of village UCI. The dependent variable is the characteristics of the village midwifes ( age, background of the knowledge, work experiences, employment status, training and double/dual duty), knowledge, action and attitude. There are significant differences in some variables of obstetricians such as the work experiences (p=0,023), the employment status (p=0,030), the double/dual duty (p=0,013), the knowledge (p=0,003), the action (p=0,017), and the behavior (p=0,045). Meanwhile, several variables have not significant differences, such as the age (p=0,193), the knowledge (p=0,185), the training activity (p=0,762), and the behavioral (0,219). Based on the brief explanation above, we can draw the conclusion that there are the differentiations in UCI village as well as non UCI village from the officers including the factors of the work experiences, the staffing, the double duty, the knowledge, the action and behavior. The policy so that the obstetricians will focus on running the programs in accordance with the skills.Keywords: the characteristic, the duty, the behavioral, the status of UCI Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  villages, the village midwifes.